Pengaruh Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Salah Satu Merek Sepatu Wanita Di Kota Bandung - Rika Wahyuni; Irena Larashati; Ashila Dwiyanisa; Asep Rochyadi Suherman (Center of Research, STIE Pasundan, Bandung, Indonesia., 2022)
This research is motivated by the not-yet-optimal purchasing decision for one brand of women's shoes in Bandung, where the main influencing factors are product quality and price. So researchers researched to find out how Product Quality, Price, and Purchase Decisions for one brand of women's shoes in the city of Bandung. This research aims to optimize product quality and price in purchasing decisions for one brand of women's shoes in Bandung. This research uses a descriptive method. The purpose of descriptive research is to test hypotheses or answer questions related to the status of the subjects studied. Moreover, this study's analytical methods are Path analysis, F-test, T-test, and coefficient of determination (R²). The results showed that product quality has a positive effect on purchasing decisions, with results showing a total effect of 32.8%. On the other hand, price positively affects purchasing decisions, with results showing a total effect of 31.5%. The research results on the relationship of the coefficient of determination (R²) expressed in percentages illustrate the magnitude of Product Quality and Price on Purchasing Decisions of 0.643 or 64.3%. In comparison, the determinant factor others that influence purchasing decisions that are not examined are indicated by the value of ɛ = 0.357 or 35.7%. Therefore, the conclusion of the suggestions that can be considered related to the research results is to pay more attention to product quality and price so that companies better understand and know consumer needs.